Pest-fauna of grasslands and seed-grass varieties - Bürgés, György (Acta Agraria Debreceniensis, 2014)
The present paper deals with various herbivorous species living in grassland ecosystems. The research focused not only on the complexity of pests in grasslands but also on individual pest species; their biology and the severity of damage, with special regard to seed feeders of some frequent herd’s grass species. The observed pests are showed in two ways, both taxonomically and according to their localization on the crop that is where they cause damage. An attempt was made to present the results being easily understandable for practitioners.